KOMPOSISI KELIMPAHAN DAN STRUKTUR KOMUNITAS FITOPLANKTON DI KAWASAN PANTAI SEKOTONG, NUSA TENGGARA BARAT - DAMAI DINIARIWISAN; THOY BATUN CITRA RAHMADANI (Universitas Mahasaraswati K. Mataram, 2024)
The potential for coastal resources in the Sekotong region, West Nusa Tenggara is very large both from an ecological and economic perspective. Various types of aquatic biota, both macroorganisms and microorganisms such as phytoplankton, can be found in this area. Phytoplankton can generally be used as a bioindicator to monitor water conditions, pollution and eutrophication. This research aims to determine the composition of the abundance and community of phytoplankton in the Sekotong coastal area. This research was carried out in January 2023 using a descriptive method, namely taking and measuring samples in the field and then describing the results. The highest phytoplankton abundance results obtained were 8640 cells/l, which is included in the oligotrophic or low category. Meanwhile, the phytoplankton composition found consisted of Chrysophyta and Cyanophyta. The results of the dominance index range from 0.19 to 0.34, which means low dominance, while the diversity index ranges from 0.91 to 1.71, which means moderate diversity. Water quality conditions show normal water values. So in general, the condition of the phytoplankton community in the Sekotong Beach area is still in the normal category with low abundance.